Development of Tourist Village Based on Local Wisdom - KOMARIAH, Neneng; SAEPUDIN, Encang; RODIAH, Saleha (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.v9.6(30).05, 2019)
Area of Paledah Village at Padaherang Sub-district in Pangandaran Regency has a potential as rural tourism. The village has interesting natural characteristics, and unique social and cultural life. This potential should be encouraged and developed in accordance with the socio-cultural characteristics of the community. The development of potential community-based tourism is a strategic effort in building the community. Rural tourism development is a long-term and potential investment for the government as the community resources and natural resources are readily available. The purpose of research is to know the development of tourism village based on local wisdom, especially related to the concept of tourism village criteria in Paledah village. This research uses qualitative approach. The data collection technique used interview, observation, F G D, and literature study. It used descriptive data analysis technique and the steps aredata reduction and presentation, and conclusion. Test of Validity and reliability used triangulation process. Informants in this study were the government, tourism village communities, and tourism developers. The number are 9 persons. The results indicate the values of local wisdom in developing agro tourism village in Pangandaran regency is embodied in organizational principles. There are three basic principles: membership is voluntary and open, management is democratic, and self-reliant. Tourism village criteria include attraction, accessibility, public facilities and tourism facilities, community empowerment, and marketing or promotion. Of the five criteria tourism village in Paledah village, two of it have been running well.Those are the attraction of tourism and community empowerment. While the other three criteria still have constraints.